Situation analysis of ECCD-F1KD initiatives in the province of Samar - Aubrey D. Tabuga; Carlos C. Cabaero (Philippine Institute for Development Studies (PIDS), 2019)
Children are more likely to develop and reach their full potential when they are protected from disease, provided proper nutrition, and live in stimulating and safe environments. Unfortunately, many children are deprived of nurturing care and favorable environment. In the Philippines, one-third of children under five years old were stunted based on 2015 estimates. This study aims to contribute in determining appropriate strategies for early childhood care and development interventions (ECCD) for the first 1000 days in a child's life by conducting a situation analysis in selected local government units in the province of Samar. It aims to examine the contextual factors underlying ECCD-F1KD interventions with emphasis on the policy and governance, the inputs and processes of planning and implementation of ECCD-F1KD programs and services, and the nurturing care practices of parents and caregivers. Results from the study emphasize, among others,the need for greater focus and resources to address current malnutrition problems and prevent malnutrition among children in the future. Likewise, there is a need for more integratedplanning amongst local offices and clearer delineation of roles for ECCD F1KD initiatives. There is also a need to establish objective metrics during planning and implementation, as well as capacitation of LGUs to conduct monitoring and evaluation. The capacity of the human resources and health infrastructure must also be improved through ample capacitation and compensation for personnel, as well as rethinking deployment of health workers and positioning of health facilities to improve access to health and nutrition services. Finally, initiatives must be designed to improve health and nutrition knowledge of parents, to provide safe environments for children, and to promote sustainable livelihoodsso that households can better provide nurturing care.
Keywords: 330; early childhood care and development; children; nurturing care practices; policy and governance; program and service delivery